RADIO, TELEWIZJA I INTERNET JAKO INSTRUMENTY PROWADZENIA DYPLOMACJI PUBLICZNEJ STANÓW ZJEDNOCZONYCH AMERYKI PÓŁNOCNEJ - Kamil Glinka (In Gremium. Studies in History, Culture and Politics, 2011)
RADIO, TELEVISION AND THE INTERNET AS INSTRUMENTS OF CONDUCTING PUBLIC DIPLOMACY BY THE UNITED STATES OF AMERICAThe United States of America is involved in broadly-understood activities in particular regions of the world. One of such activities is public diplomacy. In this context, there are well-founded reasons for a synthetic presentation of the main media: radio stations, TV stations, websites that fulfill the tasks of American public diplomacy. Especially if you consider the fact that the significance of such media' s influence grows, on the one hand, wich the increase of US' engagement on the global arena and, on the other hand, wich the defining of American foreign diplomacy's priorities.